2022
DOI: 10.3390/brainsci12060698
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Ten Different Exercise Interventions on Motor Function in Parkinson’s Disease Patients—A Network Meta-Analysis of Randomized Controlled Trials

Abstract: Objective: The aim of this study was to evaluate ten exercise interventions (YOGA: yoga training, RT: resistance training, AQU: aquatic training, TAI: Taiji Qigong training, TRD: treadmill training, VR: virtual reality training, DANCE: musical dance training, WKT: walking training, CYC: cycling training, BDJ: Baduanjin Qigong training) on motor function in Parkinson’s disease (PD) patients. Design: Through searching PubMed, Embase, Cochrane Library, Web of Science, and CNKI, only randomized controlled trials (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 95 publications
6
7
0
Order By: Relevance
“…This may be correlated to the limited number of studies included in that study (merely three studies). 37 In addition, the conclusions of the present review were similar to those reported by another review, in which Baduanjin practice is beneficial for balance and trunk flexibility. However, that study included a population of healthy or people with different types of diseases.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This may be correlated to the limited number of studies included in that study (merely three studies). 37 In addition, the conclusions of the present review were similar to those reported by another review, in which Baduanjin practice is beneficial for balance and trunk flexibility. However, that study included a population of healthy or people with different types of diseases.…”
Section: Discussionsupporting
confidence: 88%
“…The present findings are contrary to Hao’s review, which explored the effects of 10 different exercise interventions on motor function in PD, and revealed that Baduanjin has no benefit for patients with PD. This may be correlated to the limited number of studies included in that study (merely three studies) 37. In addition, the conclusions of the present review were similar to those reported by another review, in which Baduanjin practice is beneficial for balance and trunk flexibility.…”
Section: Discussionsupporting
confidence: 86%
“…Concerning motor aspects, after treatment, we observed an improvement in global motor functioning (MDS-UPDRS—part III) and a reduction in the disability of the upper limbs (DASH), which was maintained at follow-up. These data are in line with evidence reported in the literature [ 62 , 63 , 64 ].…”
Section: Discussionsupporting
confidence: 93%
“…The size of each node and the width of connecting lines are proportional to the number of studies ( 20 )。To help explain the diagnostic performance, the Surface Under the Cumulative Ranking Curve (SUCRA) ( 21 ) was used to calculate the probability of each urine marker and was the most efficient diagnostic method based on a Bayesian approach using probability values, the greater the SUCRA value, the higher the diagnostic performance rating of the urine marker. This study used a funnel plot test to determine publication bias ( 22 ). If the inverted funnel plot is asymmetric, publication bias may exist; otherwise, there is no apparent publication bias.…”
Section: Methodsmentioning
confidence: 99%